Analisis Gangguan Monyet Ekor Panjang (Macaca fascicularis) di Dusun Pengkol, Desa Sriharjo, Kecamatan Imogiri, Kabupaten Bantul, Daerah Istimewa Yogyakarta - Nurfiqri, Rika Laila; Falah, M. Darul; Nugraha, Nanda Satya (Fakultas Kehutanan Institut Pertanian STIPER Yogyakarta, 2025)
The disturbance of long-tailed monkeys (Macaca fascicularis) in Pengkol Hamlet, Sriharjo Village, Imogiri District, Bantul Regency originated from the monkeys' natural habitat adjacent to residential areas. Efforts to find sustainable solutions in Pengkol Hamlet are becoming increasingly important in reducing the disturbance caused by long-tailed monkeys. The purpose of this study was to analyze the disturbance caused and the reasons why long-tailed monkeys descend into residential areas in Pengkol Hamlet, analyze the damage caused by the long-tailed monkey disturbance, and analyze the strategies implemented by the Pengkol Hamlet community and the Sriharjo Village government in dealing with the long-tailed monkey disturbance. The sampling method employed was a combination of purposive sampling and snowball sampling. The results showed that the cause of long-tailed monkeys descending into residential areas in Pengkol Hamlet was to search for food due to the dwindling food sources in the forest area. The types of disturbances caused included monkeys entering residential areas, damaging or eating crops, and disturbing livestock, such as eggs and chicks. Estimated material losses suffered by residents due to long-tailed monkey disturbances range from less than Rp100,000 to Rp100,000 to Rp500,000. Strategies employed by the community include driving them away with loud noises, erecting fences or nets, covering bananas with sacks, throwing objects, using poles, and using slingshots. Strategies employed by the Sriharjo Village government include creating tourist attractions, planting fruit trees in the forest, and monkey conservation.